Design of the Bengawan Unmanned Vehicle (UV) Roboboat: Mandakini Neo - Nubli, Haris; Utomo, Fahri Setyo; Diatmaja, Hananta; Prabowo, Aditya Rio; Ubaidillah, Ubaidillah; Susilo, Didik Djoko; Wibowo, Wibowo; Muttaqie, Teguh; Laksono, Fajar Budi (Mekanika: Majalah Ilmiah Mekanika, 2022)
Mandakini Neo was made with the ship's capacity, speed, and comfort in mind, as well as the ship's hydrodynamic performance and construction cost. Therefore, the method used to determine the hydrostatic characteristics is through a simulation consisting of a resistance test, stability test, maneuver test, and seakeeping test. The simulation uses Maxsurf software with the Savitsky method, which is then processed by data. Global Positioning System (GPS) and ultrasonic sensor tests were also conducted. Based on the simulation results, the stability of the Mandakini Neo ship has a GZ value of 0.1417 m with an angle of 30°, which follows the standards of the International Maritime Organization (IMO). In testing, the maneuvers obtained have met IMO standards based on tactical and advanced diameters. Based on the seakeeping test, when the speed is 5 knots, the heave movement has the same magnitude for all wave headings, 0.0096 m. while the most considerable rolling motion is in the wave direction of 135°, which is 0.36 m, and the most considerable pitch motion is in the direction of the 180° wave, which is 0.042 m. At a speed of 10 knots, the heave motion produced is the same as for all wave headings.